2011
DOI: 10.1188/11.onf.e97-e106
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pilot Test of a Simultaneous Stage-Matched Exercise and Diet Intervention for Breast Cancer Survivors

Abstract: Nurse-led lifestyle interventions may improve QOL for cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 39 publications
1
106
0
4
Order By: Relevance
“…The majority of participants in the review were white with a mean age of 49 years. Two studies included only non-white participants [27, 28], while the remaining studies included white or ethnically mixed populations (Table 1). Based on reported data, the estimated mean time since diagnosis across studies was 2.6 years.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of participants in the review were white with a mean age of 49 years. Two studies included only non-white participants [27, 28], while the remaining studies included white or ethnically mixed populations (Table 1). Based on reported data, the estimated mean time since diagnosis across studies was 2.6 years.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Mock et al 9 found that a 6-week home-based walking program prescribed and monitored by oncology nurses was effective in improving symptom intensity, anxiety, and sleep in early-stage breast cancer patients on radiation therapy. Similarly, Kim et al 8 found that a 12-week-long nurse-led physical activity and diet intervention resulted in significant improvements in physical activity and diet readiness for change and quality-of-life indices in breast cancer survivors. The authors of both studies concluded that involving oncology nurses in physical activity interventions may be an effective means of improving quality-of-life outcomes in cancer patients.…”
mentioning
confidence: 95%
“…[15][16][17][18][19] Kim et al 4 in 2011, investigated the feasibility and preliminary effects of a simultaneous stagematched exercise and diet (SSED) intervention in breast cancer survivors through a randomized, controlled trial in South Korea. Their samples were 45 women with breast cancer who completed their cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Breast cancer and its treatments often are associated with adverse effects that can persist for years and decrease health related quality of life (QOL). 4 Recently, besides measurable tumor parameters, the subjective perception regarding quality of life has become an important therapeutic objective. This is true both in the early stages when women seek to participate in everyday life and in the metastatic setting.…”
Section: Introductionmentioning
confidence: 99%